Postcolonial Witnessing - Craps, Stef (Palgrave Macmillan Limited, 2013)
Postcolonial Witnessing argues that the suffering engendered by colonialism needs to be acknowledged more fully, on its own terms, in its own terms, and in relation to traumatic First World histories if trauma theory is to have any hope of redeeming its promise of cross-cultural ethical engagement
Description based on publisher supplied metadata and other sources
Keywords: African literature; Psychisches Trauma; Englisch; Postkoloniale Literatur